Effectiveness of fluoroscopy-guided intra-articular steroid injection for hip osteoarthritis. Issue 11 (November 2015) - Subedi, N.; Chew, N.S.; Chandramohan, M.; Scally, A.J.; Groves, C.
<x xml:space="preserve">Abstract</x> Aim To demonstrate the benefits of fluoroscopy-guided intra-articular steroid injection in the hip with varying degrees of disease severity, and to investigate the financial aspects of the procedure and impact on waiting time. Materials and methods A prospective study was undertaken of patients who underwent fluoroscopic intra-articular steroid injection over the 9-month study period. Comparative analysis of the Oxford hip pain score pre- and 6–8 weeks post-intra-articular injection was performed. Hip radiographs of all patients were categorised as normal, mild, moderate, or severe disease (four categories) based on the modified Kellgren–Lawrence severity scale, and improvement on the Oxford hip pain score on each of these four severity categories were assessed. Results Within the study cohort of 100 patients, the mean increase in post-procedure hip score of 7.32 points confirms statistically significant benefits of the therapy (p<0.001, 95% confidence interval: 5.55–9.09). There was no significant difference in pre-injection hip score or change in score between the four severity categories (p=0.51). Significant improvement in hip score (p<0.05) was demonstrated in each of the four severity categories 6–8 weeks post-injection. No associated complications were observed. Conclusion The present study confirms that fluoroscopy-guided intra-articular steroid injection is a highly effective therapeutic measure for hip osteoarthritis across all grades of disease severity with significant cost savings and the potential to reduce waiting times.